2006
DOI: 10.1213/01.ane.0000200282.38041.1f
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Emergence Agitation After Sevoflurane Anesthesia for Pediatric Cerebral Magnetic Resonance Imaging by Small Doses of Ketamine or Nalbuphine Administered Just Before Discontinuing Anesthesia

Abstract: Magnetic resonance imaging (MRI) requires long-lasting immobilization that frequently can only be provided by general anesthesia in pediatric patients. Sevoflurane provides adequate anesthesia but many patients experience emergence agitation. Small doses of ketamine and nalbuphine provide moderate sedation but their benefits have subsided at the time of emergence. We hypothesized that delaying their administration until the end of the procedure would prevent emergence agitation without prolonging patient wake-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
1
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(71 citation statements)
references
References 24 publications
2
63
1
5
Order By: Relevance
“…Volatile anesthetics such as sevoflurane and desflurane have been known to aggravate emergence delirium because of their rapid recovery. Dalens et al [17] suggested that small doses of ketamine or nalbuphine administered just before discontinuing anesthesia could prevent emergence delirium. Oral clonidine 4 μg/kg prior to induction has been shown to decrease emergence delirium compared with midazolam 0.5 mg/kg [18].…”
Section: Discussionmentioning
confidence: 99%
“…Volatile anesthetics such as sevoflurane and desflurane have been known to aggravate emergence delirium because of their rapid recovery. Dalens et al [17] suggested that small doses of ketamine or nalbuphine administered just before discontinuing anesthesia could prevent emergence delirium. Oral clonidine 4 μg/kg prior to induction has been shown to decrease emergence delirium compared with midazolam 0.5 mg/kg [18].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, there are reports showing that fentanyl, nalbuphine, midazolam, and lidocaine are effective in reducing emergence agitation (Galinkin et al, 2000;Cohen et al, 2001;Dalens et al, 2006;Kim et al, 2011;Seo et al, 2011). In our study, nalbuphine 10 mg was to be administered iv when a state of emergence agitation continued for more than 3 min, which if necessary, could be used again after 3 h. However, the state of emergence agitation in both groups only lasted about 1 min, so additional administration of medication was unnecessary.…”
Section: Discussionmentioning
confidence: 99%
“…This issue predominantly concerns pre-school children; its cause has not been fully elucidated, but post-sevoflurane excitation is estimated to occur in over 30% of children undergoing general anaesthesia with sevoflurane for non-surgical procedures [15,16]. The incidence of excitation following anaesthesia can be reduced by using propofol, ketamine or nalbuphine during the final stage of anaesthesia [15,17,18]. Nalbuphine in a dose of 0.1 mg kg -1 administered at the end of anaesthesia has been shown to decrease the incidence of excitation and anxiety after anaesthesia more effectively than ketamine without prolonging the awakening time [18].…”
Section: Other Applications Of Nalbuphinementioning
confidence: 99%
“…The incidence of excitation following anaesthesia can be reduced by using propofol, ketamine or nalbuphine during the final stage of anaesthesia [15,17,18]. Nalbuphine in a dose of 0.1 mg kg -1 administered at the end of anaesthesia has been shown to decrease the incidence of excitation and anxiety after anaesthesia more effectively than ketamine without prolonging the awakening time [18].…”
Section: Other Applications Of Nalbuphinementioning
confidence: 99%